Studi Semi-Systematic Review terhadap Persepsi Penggunaan, Persepsi Kemanfaatan dan Kepercayaan Sebagai Prediktor Kepuasan Penyediaan Barang/Jasa LPSE di Indonesia - Milde Wahyu; Jonner Simarmata (Universitas Batanghari Jambi, 2022)
The implementation of electronic procurement of goods and services (e-procurement) in Indonesia has proven to reduce costs and increase time efficiency. Unfortunately, the level of satisfaction of stakeholders with the Electronic Procurement Service (LPSE) is still lacking. This study was prepared based on the semi-systematic review method because it intends to detect themes, theoretical perspectives, and general problems related to various predictors of satisfaction with LPSE goods/services providers in Indonesia. The practice of e-procurement is considered suitable to be approached by the TAM (Technology Acceptance Model) model which then needs to identify two basic beliefs that influence the use of the technology, namely perceived easy use and perceived usefulness. This study also includes the construct of confidence as a good novelty that has the potential as a moderating variable. The contributions/outputs of this study are in the form of a map of the research area, a synthesis of the state of knowledge, and an agenda for further research or a historical review or timeline of the e-procurement topic. The results of the study can be used by subsequent researchers as a research foothold.